Concierto navideño. (UNED, 2023)
Actividad de funcionarios en concierto navideño.Se obervan: Lizette Brenes Bonilla ; Victor Hugo Fallas Araya; Arias Camacho, Rodrigo; Roxana Cubero; Elías Badilla Meléndez; Alexandra Abarca Chinchilla; Silvia Abdelnour Esquivel